2020
DOI: 10.4103/aam.aam_61_19
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, attitude, and understanding toward epilepsy among workers in a State Specialist Hospital in Maiduguri, Northeastern Nigeria

Abstract: Background: Epilepsy is a common presentation at clinics in Psychiatric Hospitals, Teaching Hospitals, and general practice. In developing countries and Africa especially, awareness, attitude, and understanding are generally poor. People still believe in spirits as the cause of epilepsy. Objectives: The objectives were to assess the awareness; attitude and knowledge of Hospital workers in general practice concerning epilepsy. Methodology: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(12 reference statements)
0
3
1
Order By: Relevance
“…This study aimed at improving community participation in clinical trials in Ghana by evaluating the knowledge, attitudes and perceptions towards participation in clinical trials among respondents in the New Juaben South Municipal Assembly. There were more males than females in this study which compares with other similar surveys which all reported more male respondents than females [ 19 , 20 ]. This observation could probably be due to higher uptake of research among males than females.…”
Section: Resultscontrasting
confidence: 64%
“…This study aimed at improving community participation in clinical trials in Ghana by evaluating the knowledge, attitudes and perceptions towards participation in clinical trials among respondents in the New Juaben South Municipal Assembly. There were more males than females in this study which compares with other similar surveys which all reported more male respondents than females [ 19 , 20 ]. This observation could probably be due to higher uptake of research among males than females.…”
Section: Resultscontrasting
confidence: 64%
“…Seven articles were subsequently excluded for various reasons: one lacked full-text access [ 18 ], two had unclearly written methods [ 19 , 20 ], and the remaining four had outcomes unrelated to this study [ 21 – 24 ]. Finally, 21 studies were included in this systematic review and meta-analysis [ 4 , 25 – 44 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one eligible studies included in the meta-analysis were published between 1981 and 2023. Of these 21 published original studies that reported the proportion of mortality, four were conducted in Ethiopia [ 26 , 29 , 39 , 40 ], and the majority of studies (nine) were conducted in Nigeria [ 4 , 25 , 27 , 28 , 33 37 ]. The other studies were conducted in Tanzania (three) [ 30 , 31 , 43 ], South Africa (two) [ 41 , 42 ], Cameroon (one) [ 32 ], Senegal (one) [ 44 ], and Sudan (one) [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Associated injuries play an important role in determining the outcome of a chest injury patient especially when a head injury is associated. 6 The management has several essential elements, such as adequate prehospital care, rapid transport to a specialized center, complex in-hospital care, and rehabilitation. The prehospital phase is vital in determining treatment outcomes appropriately and contributes significantly to reducing morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%